Assessing Benthic Responses to Fishing Disturbance Over Broad Spatial Scales That Incorporate High Environmental Variation - Lundquist, Carolyn J.; Bowden, David; Cartner, Katie; Stephenson, Fabrice; Tuck, Ian; Hewitt, Judi E. (Frontiers in Marine Science, 2018)
Marine benthic habitats are modified by a number of human-related disturbances. When these disturbances occur at large scales over areas of high environmental variability, it is difficult to assess impacts using metrics such as species richness or individual species distributions because of varying species-specific responses to environmental drivers (e.g., exposure, sediment, temperature). Impact assessment can also be problematic when assessed at broad spatial scales because of regional heterogeneity of species pools. Even when effects on individual species can be detected, it is difficult to upscale from individual species to ecosystem scale effects. Here, we use a functional group approach to assess broad scale patterns in ecological processes with respect to fishing and environmental drivers. We used data from field surveys of benthic communities from two large, widely separated areas in New Zealand’s EEZ (Chatham Rise and Challenger Plateau). We assigned 828 taxonomic units (most identified to species) into functional groups related to important ecosystem processes and likely sensitivity to, and recovery from, fishing disturbance to the seafloor. These included: opportunistic early colonists; substrate stabilisers (e.g., tube mat formers); substrate destabilisers; shell hash-creating species; emergent epifauna; burrowers; and predators and scavengers. Effects of fishing disturbance on benthic functional composition were observed, even at this broad spatial scale. Responses varied between functional groups, with some being tolerant of fishing impacts and others showing rapid declines with minimal fishing effort. The use of a functional group approach facilitates assessment of impacts across regions and species, allowing for improved generalisations of impacts to inform management and decision making.